The Behavioral Ecology of the Tibetan Macaque - Li, Jin-Hua; Sun, Lixing; Kappeler, Peter M. (Fascinating Life Sciences,, 2020)
This open access book summarizes the multi-disciplinary results of one of China's main primatological research projects on the endemic Tibetan macaque (Macaca thibetana), which had continued for over 30 years, but which had never been reported on systematically. Dedicated to this exceptional Old World monkey, this book makes the work of Chinese primatologists on the social behavior, cooperation, culture, cognition, group dynamics, and emerging technologies in primate research accessible to the international scientific community. One of the most impressive Asian monkeys, and the largest member of its genus, the Tibetan macaque deserves to be better known. This volume goes a long way towards bringing this species into the spotlight with many excellent behavioral analyses from the field.- Frans de Waal, Professor of Psychology, Emory University, USA. Macaques matter. To understand primate patterns and trends, and to gain important insight into humanity, we need to augment and expand our engagement with the most successful and widespread primate genus aside from Homo. This volume focuses on the Tibetan macaque, a fascinating species with much to tell us about social behavior, physiology, complexity and the macaque knack for interfacing with humans. This book is doubly important for primatology in that beyond containing core information on this macaque species, it also reflects an effective integrated collaboration between Chinese scholars and a range of international colleagues-exactly the type of collaborative engagement primatology needs. This volume is a critical contribution to a global primatology. - Agustín Fuentes, Professor of Anthropology, University of Notre Dame, USA. I have many fond memories of my association with Mt. Huangshan research beginning in 1983, when together with Professor Qishan Wang we established this site. It is such a beautiful place and I miss it. It is gratifying to see how far research has progressed since we began work there, becoming more internationalized and very much a collaborative endeavor under the long-term direction of Professor Jin-Hua Li and colleagues. This book highlights the increased interest in this species, representing a variety of disciplines ranging from macro aspects of behavior, cognition and sociality, to micro aspects of microbes, parasites and disease, authored by a group of renowned Chinese and international primatologists. I applaud their efforts and expect more interesting work to come from this site in the years ahead.- Kazuo Wada, Professor Emeritus, Kyoto University, Japan.